2013
DOI: 10.1155/2013/814973
|View full text |Cite
|
Sign up to set email alerts
|

Posttransplant Lymphoproliferative Disease after Pediatric Solid Organ Transplantation

Abstract: Patients after solid organ transplantation (SOT) carry a substantially increased risk to develop malignant lymphomas. This is in part due to the immunosuppression required to maintain the function of the organ graft. Depending on the transplanted organ, up to 15% of pediatric transplant recipients acquire posttransplant lymphoproliferative disease (PTLD), and eventually 20% of those succumb to the disease. Early diagnosis of PTLD is often hampered by the unspecific symptoms and the difficult differential diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
101
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 133 publications
5
101
1
Order By: Relevance
“…There may be a higher risk of developing PTLD with tacrolimus than cyclosporine, but some studies (mostly retrospective) show no difference between the drugs. 8 In the present study, the frequency of PTLD was similar between patients who received tacrolimus or cyclosporine, but the frequency of PTLD was higher in children who received tacrolimus and adults who received cyclosporine. The transplant organ type may indirectly affect the risk of developing PTLD because the intensity of immunosuppression may differ between organ graft types; recipients of heart, lung, and intestinal grafts may require the most intensive immunosuppression and may be at higher risk for development of PTLD than recipients of other organ types.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…There may be a higher risk of developing PTLD with tacrolimus than cyclosporine, but some studies (mostly retrospective) show no difference between the drugs. 8 In the present study, the frequency of PTLD was similar between patients who received tacrolimus or cyclosporine, but the frequency of PTLD was higher in children who received tacrolimus and adults who received cyclosporine. The transplant organ type may indirectly affect the risk of developing PTLD because the intensity of immunosuppression may differ between organ graft types; recipients of heart, lung, and intestinal grafts may require the most intensive immunosuppression and may be at higher risk for development of PTLD than recipients of other organ types.…”
Section: Discussionsupporting
confidence: 42%
“…8 Additional factors such as extranodal disease, stage, and number of disease sites may correlate with clinical outcome. In the present patients, mean survival time was shorter for patients who tested positive than negative for Epstein-Barr virus-encoded small RNA, but there was no relation between survival and other risk factors such as extranodal involvement or number of disease sites.…”
Section: Discussionmentioning
confidence: 99%
“…Most reported descriptions of T-and NK-cell posttransplant lymphoproliferative disorder (100 to 200 cases) were single case reports, and few reports included > 3 patients. [4][5][6]10,13 A higher incidence of posttransplant lymphoproliferative disorder may occur in children than adults because children typically are seronegative for Epstein-Barr virus. 12 …”
Section: Discussionmentioning
confidence: 99%
“…4 Mono-morphic T-cell posttransplant lympho-proliferative disorder is uncommon in children, and literature review showed only 19 pediatric T-cell posttransplant lymphoproliferative disorders that have been reported. 5,6 We treated a patient who had a rare T-ALL/T-LBL after liver transplant.…”
Section: Introductionmentioning
confidence: 99%
“…Monomorphic type PTLD corresponds to the lymphoma type in the immunocompetent host and has the same criteria for diagnosis. Most are of B‐cell origin, with diffuse large B‐cell lymphoma (DLBCL) being the most common . In adults, sinusoidal invasion of malignant CD30+ B cells in patients diagnosed with de novo DLBCL is associated with poor prognosis .…”
Section: Introductionmentioning
confidence: 99%